Multi‑criteria Analysis of the Competitiveness of Major Baltic Sea Container Terminals - Bartosiewicz, Aleksandra; Jadczak, Radosław (Comparative Economic Research. Central and Eastern Europe, 2023)
The rapid growth in the volume of international container transport requires that the entire transport chain become more competitive, including maritime container terminals. The aim of the article is to identify the number and location of major Baltic container terminals and to perform a multi‑criteria analysis of the competitiveness of maritime container terminals in the Baltic Sea Region (BSR). In our study, we perform the AHP multi‑criteria analysis with subjective criteria weights, as well as the entropy method with objective criteria weights. Thus, we can evaluate the competitive advantages of each of the specified terminals in the region. We are among the first to study the competitiveness of individual maritime container terminals in the BSR. Thus, our research adds to the literature that has yielded results on the competitive advantage of the Baltic seaports.